HIV prevalence, previous HIV testing, and condom use with clients and regular partners among Senegalese commercial sex workers. Issue 7 (17th October 2007) - Wang, C; Hawes, S E; Gaye, A; Sow, P S; Ndoye, I; Manhart, L E; Wald, A; Critchlow, C W; Kiviat, N B
Abstract : Objectives: To assess HIV prevalence and risk factors for HIV infection, to investigate condom use among registered female commercial sex workers (CSWs) in Senegal, West Africa, and to examine the association between previous HIV testing, knowledge of HIV serostatus and condom use with both regular sex partners and clients within this population. Methods: A cross-sectional study was conducted at three sexually transmitted disease clinics among 1052 Senegalese registered CSWs between 2000 and 2004. Inperson interviews soliciting information concerning demographic characteristics, medical history, sexual behaviour with clients and regular partners, and previous HIV testing history were performed. Blood samples were collected for determination of HIV-1 and/or HIV-2 serostatus. Multivariable, Poisson and log-binomial models were used to calculate prevalence ratios. Results: The overall HIV prevalence was 19.8%. Over 95% of CSWs reported always using a condom with clients, but only 18% reported always using a condom with their regular partners. A history of previous HIV testing was not associated with condom use with clients (adjusted prevalence ratio (APR) = 0.98, 95% confidence intervals, CI: 0.90 to 1.06). However, prior HIV testing was associated with decreased condom use with their regular partners (APR = 0.44, 95% CI: 0.28 to 0.69), especially in women who tested HIV negative (APR = 0.17, 95% CI: 0.08 to 0.36). Conclusions: CSWs in Senegal have a high HIV prevalence; therefore preventing HIV transmission from this population to the general population is important. Condom use with regular partners is low among registered CSWs in Senegal, and a prior HIV negative test is associated with even less condom use with regular partners. Intervention efforts to increase condom use with regular sexual partners are needed.